Forging Responsible Unions: Metal Workers and the Rise of the Labour Injunction in Canada - Tucker, Eric; Fudge, Judy (Labour/Le Travailleur, 1996)
At the turn of the century, the legislative, administrative, and judicial branches of the Canadian state responded to the labour conflicts associated with the second industrial revolution by simultaneously expanding both their coercive and their facilitative roles. This paper examines one aspect of this development, the rise of the labour injunction, through a study of a series of strikes conducted chiefly by metal workers in south central Ontario between 1900 and 1914. In addition to retrieving the largely forgotten genealogy of a body of law that continues to play an important role in regulating and containing trade union activity, the study contributes insights into debates raging among labour historians regarding the role and significance of state institutions and public discourse in determining the trajectory and fate of organized labour.